2007
DOI: 10.1523/jneurosci.4152-06.2007
|View full text |Cite
|
Sign up to set email alerts
|

Phasic Dopamine Release Evoked by Abused Substances Requires Cannabinoid Receptor Activation

Abstract: Transient surges of dopamine in the nucleus accumbens are associated with drug seeking. Using a voltammetric sensor with high temporal and spatial resolution, we demonstrate differences in the temporal profile of dopamine concentration transients caused by acute doses of nicotine, ethanol, and cocaine in the nucleus accumbens shell of freely moving rats. Despite differential release dynamics, all drug effects are uniformly inhibited by administration of rimonabant, a cannabinoid receptor (CB 1 ) antagonist, su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

22
311
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 330 publications
(333 citation statements)
references
References 33 publications
22
311
0
Order By: Relevance
“…Screening of two independent clinical populations revealed that CB 1 gene variants are associated with nicotine dependence (Chen et al, 2008) and the CB 1 receptor antagonist Rimonabant (SR141716A) prolonged abstinence rates in smokers expressing motivation to quit . SR141716A and the related CB 1 antagonist AM251 reduce nicotine selfadministration (SA) by rats (Cohen et al, 2002(Cohen et al, , 2005Forget et al, 2009;Shoaib, 2008), attenuate nicotine-induced increases in nucleus accumbens (NAc) dopamine (DA) (Cheer et al, 2007;Cohen et al, 2002;Grieder et al, 2012), and reduce reinstatement of nicotine-seeking behavior in animal models of relapse (Forget et al, 2009). Collectively, these findings provide strong evidence for a CB 1 receptor involvement in the motivational effects produced by nicotine, and imply a role for endocannabinoid (eCB) signaling in this process.…”
Section: Introductionmentioning
confidence: 92%
“…Screening of two independent clinical populations revealed that CB 1 gene variants are associated with nicotine dependence (Chen et al, 2008) and the CB 1 receptor antagonist Rimonabant (SR141716A) prolonged abstinence rates in smokers expressing motivation to quit . SR141716A and the related CB 1 antagonist AM251 reduce nicotine selfadministration (SA) by rats (Cohen et al, 2002(Cohen et al, , 2005Forget et al, 2009;Shoaib, 2008), attenuate nicotine-induced increases in nucleus accumbens (NAc) dopamine (DA) (Cheer et al, 2007;Cohen et al, 2002;Grieder et al, 2012), and reduce reinstatement of nicotine-seeking behavior in animal models of relapse (Forget et al, 2009). Collectively, these findings provide strong evidence for a CB 1 receptor involvement in the motivational effects produced by nicotine, and imply a role for endocannabinoid (eCB) signaling in this process.…”
Section: Introductionmentioning
confidence: 92%
“…Drugs of abuse increase dopaminergic transmission in the NAc (Cheer et al, 2007;Daberkow et al, 2013;Di Chiara and Imperato, 1988;Phillips et al, 2003;Volkow et al, 2007), which contributes to their acutely reinforcing properties. We used a dose of morphine that, when paired with precipitated withdrawal, generates rapid dependence in rats (Schulteis et al, 1999).…”
Section: Morphine-exposure Increases Dopaminergic Transmission In Thementioning
confidence: 99%
“…The mesolimbic dopamine system is implicated in reinforcement learning, goal-directed behavior, and motivational processes, including those for abused substances (Everitt and Robbins, 2005;Kelley, 2004;Robinson and Berridge, 1993;Salmone and Correa, 2012;Schultz, 2007). Alcohol, similar to virtually all abused substances, increases dopamine transmission within the ventral striatum (Cheer et al, 2007;Di Chiara and Imperato 1986;. Importantly, the mesolimbic dopamine system continues to mature during the adolescent period (Chambers et al, 2003), suggesting that adolescent alcohol use may alter its function, resulting in abnormal reward-related learning processes that impact decision making (Alaux-Cantin et al, 2013;Casey and Jones 2010;Goudriaan et al, 2007;Johnson et al, 2008;McClory and Spear 2014;Nasrallah et al, 2011;Philpot et al, 2009;Toalston et al, 2014;Zeigler et al, 2005).…”
Section: Introductionmentioning
confidence: 99%